Hierarchical Agglomerative Clustering Algorithm method for distributed generation planning - Vinothkumar, K.; Selvan, M.P. (International journal of electrical power & energy systems, 2014)
•Hierarchical Agglomerative Clustering Algorithm (HACA) based approach is proposed for DG planning.•This method employs only single stage in identification of suitable site and size.•A guaranteed feasible solution is always available to the planner by this method.•Solution method is straightforward and accompanied by unsupervised learning and less computational complexity. Planning of distributed generator (DG) units in the distribution system employing Hierarchical Agglomerative Clustering Algorithm (HACA) is proposed in this paper. The proposed method overcomes the dependency of existing methods of DG placement, either on the entire global preference information or on the experience of the distribution system planner. The proposed method is validated with weighted sum method and its effectiveness is tested using two distribution systems of different size and configuration. The results of the simulation study demonstrate the suitability of proposed method in solving the problem involving multiple objectives in DG planning studies.